Hubungan Pengetahuan Dengan Kepatuhan Karyawan Dan Tenaga Kesehatan Terhadap Protokol Kesehatan Era New Normal Di RS Graha Medika - Hadi Nur Efendi; Andi Wapa (Jurnal Anestesi, 2024)
This research began with problems in the field which indicated a lack of awareness among health workers and personnel regarding health protocols in the new normal era. This research aims to determine the relationship between knowledge or education and compliance among employees and health workers. This research uses quantitative methods by testing the relationship between variables. The research location was Graha Medika Hospital with a population of 187 and a sample of 90 using random sampling techniques. The data collection technique uses a questionnaire type with attention to validity and reliability tests. As for the results of this research, there is a significant relationship between knowledge or education and compliance by employees and health workers in maintaining health protocols. This is indicated by the statistical test results of P-Value 0.031 < 0.05.